The Role of Metaphors in the Interpretation of a Prophetic Discourse: A Linguistic Analysis on Isaiah 40-55 - Kim, Hyukki (My University, 2012)
Isaiah 40-55 deals with various important themes related to Israel's salvation. However, in spite of the great number of works on these chapters, there are still many unsolved debates. This is because chs. 40-55 are written in excellent poetic language, which, although terse, is full of imagery, parallelism, personification, and rhetorical questions. These poetic and rhetorical devices were very effective for communicating to the original audience but often prevent readers in modem times from understanding the meaning of the text. In particular, when these devices are approached from purely historical-critical perspectives, continued misunderstanding and increased debate is often the result. Taking these concerns into consideration, this project has employed a linguistic approach which deals with mental frames and cognitive metaphors which are based on the cognitive world of the ancient people. In interacting with God, who is the main speaker, the three closely related metaphors, "Jacob-Israel," "Servant," and "Zion," play a very important role in the rhetorical development of chs. 40-55. This project has tried to integrate these metaphors within the frame "the relationship between God and his people." While this frame is fundamental in the Bible, there are also various sub-frames such as king/subject, parents/children, husband/wife, judge/litigant, master/servant, shepherd/sheep, and potter/pottery. Within chs. 40-55, by employing these various subframes with three main metaphors, "Jacob-Israel," "Servant," and "Zion," the prophet tries to communicate and persuade the addressees, the exiles, to accept God's message. While the three metaphors are the main figures in the text, each of them has different connotations. In addition, they are closely related to the addressees themselves (the exiles); thus, the prophet seeks to make them identify the three figures with themselves. By observing, criticizing, and comforting these three figures, the prophet responds to the potential complaints of the exiles and persuades them to return to God.
Keywords: Prophetic discourse; Isaiah 40-55